Smart Attendance Management System - Onaifo, Frank; Okandeji, Alexander Akpofure; Eluro, Alex; Owolabi, Francis (IPTEK The Journal for Technology and Science, 2025)
The research work considered the development of an attendance system using Artifi- cial Intelligence technology. Using the Android mobile operating system developed by Google, XML, and Java programming, a smart attendance management system (SAMA) is developed for daily student attendance in colleges or schools. SAMA attempts to record attendance through face detection. Accordingly, it enhances aca- demic performance in schools as students must attain minimum attendance require- ments before they are allowed to take their examinations. It also prevents examination malpractice, such as impersonation during tests and exams. SAMA was designed and implemented using Olabisi Onabanjo University, Department of Electronic and Electrical Engineering, as a case study. Results showed that the proposed model elim- inates or reduces the time wasted during manual collection of attendance, creates a student database management system that is not prone to errors or being manipulated by users, and, above all, aids in better management of classroom statistics for alloca- tion of attendance.